La langue française À l’université algérienne : changement de statut et impact - Lamia Boukhannouche (Carnets)
In the Algerian context, education from primary to secondary is taught in Arabic and it is not until the third primary year learning French appears in programs. At university, this Arabization has been prosecuted in some academic disciplines, social sciences, economic, trade ... And most of the scientific and technical fields such as medicine, veterinary science, architecture ... teach in French. The French language is therefore access to scientific training. This means that the Algerian university, we therefore have a teaching Arabic and a francophone education. This fact is often problematic for newcomers to the university who are forced to pursue complex studies in a language they often have insufficient knowledge. That is why our paper aims to see the kind of palliative to offer new registrants essentially those of science and technology in French, namely veterinary sciences, early in their academic training. This is obviously a French education (in the form of language courses) beyond instruction in French (which concerns during the discipline). The implementation of the palliative for language training is part of the FOU (French on academic objective).